A computer-assisted environment for understanding geometry theorem proving problems and making conjectures. (13th August 2009) - Wong, Wing-Kwong; Huang, Chun-Wei; Yin, Sheng-Kai; Yang, Hsi-Hsun; Chen, Po-Yu; Hsu, Sheng-Cheng; Wu, Shih-Hung
Many students do not perform well in geometry theorem proving. Researchers indicated that the construction of the figure of a geometry problem is fundamental in understanding the problem and producing a proof. We believe that the construction of the figure of a geometry problem is fundamental in understanding the problem and producing a proof. Current dynamic geometry environments are useful for illustrating invariant conditions when a figure is changed dynamically. However, they generally neither show the construction of a figure nor allow learner to make conjectures within the environments. To address these issues, we propose a system that shows how to construct the figure of a problem step by step and allows a learner to manipulate the figure dynamically and enter the properties of the figure that they discover. For the conjectures they enter, the system can test whether the conjectures are correct or not.